A study on the buying behaviour of mobile phone by the population in the district of Tambunan / Jenus @ Clebester Gansau @ Petrus - Gansau @ Petrus, Jenus @ Clebester (2007)
This research is a study on the buying behaviour of mobile phone by the population in Tambunan District . The aims of this research is together the general information of population in Tambunan of their buying behavior on hand phone, to investigate the effective of certain demographic profile on hand phone purchase, to identify the most popular brand of hand phone, to identify the level cost implication by hand phone user, to identify the health implication, physically and psychologically on hand phone user and to develop a more effective marketing strategies to market hand phone in Tambunan District. The survey was conducted among 120 respondents in Tambunan District. All the respondents were chosen by using simple random sampling procedure. However, been selected according to profession equally distributed. The results were analyzed using SPSS for frequencies and crosstabulations. Based on the findings, crosstabulation and analysis most respondents are hand phone users. Most interesting are the health implication and cost implication which are facing by users can not stop their next purchasing of hand phone. They also willing to change into 3G function if the service available in Tambunan.